Knowledge Management, Supply Chain Marketing Implementation and Marketing Capabilities and Tourism Industry Performance in Indonesia - Adi Santoso (International Journal of Supply Chain Management, 2020)
The current study purpose is to conduct the relationship between the knowledge management (KNW), customer orientation (CUO) and tourism industry performance (TIP) of Indonesia with the moderating effect of supply chain marketing planning capabilities (SCMPC) and supply chain marketing implementations capabilities (SCMIC). For this purpose, the data was collected from the 400 professional managers by using a convenient sampling technique which yield a 80 percent response rate. The Structural Equation Modelling (SEM) analysis has shown that knowledge management (KNW) has directly significant and positive association with the tourism industry performance (TIP) but customer orientation (CUO) has an insignificant relationship with the TIP. On the other hand, the indirect effect of the study has shown that both moderating indicators namely SCMPC and SCMIC have a significant moderating effect in the relationship of both of the exogenous and endogenous variable. Therefore, this moderating effect contribution is considered to be an important contribution of the study which fill the previous studies gaps. The research limitations and future directions at the end of the study were also discussed.